A presença da religião em ações docentes de uma Escola Pública de Educação Infantil - Mak, Denise (2014)
The present study investigates how religion has been approached by kindergarten educational agents within a public school in São Paulo. To do so, concepts by Bourdieu (2004; 2011; 2012), Fernández (1995), Wallon (1975; 1995; 2008) and Vygotski (2007) are applied. During four months, four groups of a Municipal School of Children Education in the east side of São Paulo city were observed. The data collected were analyzed under the hypothesis that religion presence at schools appears as symbolic capital as well as a form of symbolic violence. Concepts of developmental psychology were also base for analysis of activities implemented by teachers. The results indicate that three of the four teachers participating in the research reflect their beliefs in the classroom, even indoctrinating their students, thus mixing their own religion with their professional life. The school as a whole also showed itself as unable to be impartial about religion, once it proposes parental interaction on Easter and presents several kinds of religious messages in its dependencies. Therefore, it concludes that religion, mainly represented by Christian beliefs, is still present in the routine of secular public school